2016
DOI: 10.1002/mnfr.201600462
|View full text |Cite
|
Sign up to set email alerts
|

Genistein and delphinidin antagonize the genotoxic effects of the mycotoxin alternariol in human colon carcinoma cells

Abstract: Our data indicate that a respective polyphenol-rich diet might aid to protect against genotoxic damages caused by AOH, whereby bioactive concentrations of DEL are predominantly expected locally in the intestines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Alternaria alternata proliferates on food items and can contaminate commodities which may also reach the market (Walravens et al 2016). Alternaria mycotoxins can differ greatly in structure and their biological targets span from the regulation of DNA topology to the estrogenic cascade (Aichinger et al 2017; Jarolim et al 2016; Lehmann et al 2006; Vejdovszky et al 2017a). Among these, the perylene quinone type mycotoxin altertoxin II (ATXII) is one of the more potent ones with respect to genotoxicity (Fleck et al 2016; Pahlke et al 2016; Schwarz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alternaria alternata proliferates on food items and can contaminate commodities which may also reach the market (Walravens et al 2016). Alternaria mycotoxins can differ greatly in structure and their biological targets span from the regulation of DNA topology to the estrogenic cascade (Aichinger et al 2017; Jarolim et al 2016; Lehmann et al 2006; Vejdovszky et al 2017a). Among these, the perylene quinone type mycotoxin altertoxin II (ATXII) is one of the more potent ones with respect to genotoxicity (Fleck et al 2016; Pahlke et al 2016; Schwarz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Polyphenols provide a wide range of anti-carcinogenic health benefits. [15][16][17][18][19][20][21][22] However, polyphenol absorption is reportedly very low.…”
Section: Introductionmentioning
confidence: 99%
“…γ‐H2AX formation is a rapid and sensitive cellular response to the presence of DSBs (Celeste et al, ; Ibuki & Toyooka, ). Previous studies had shown that 100 μM GES could induce significant genotoxicity in other cell systems (Aichinger, Beisl, & Marko, ); so here we exposed 100 μM GES for 1, 3, 6 and 9 hr to dynamically determine the number of γ‐H2AX foci in the WT TK6 cells. As shown in Figure a,b the numbers of γ‐H2AX foci were significantly increased after treatment of 100 μM GES, and peaked at 6 hr.…”
Section: Resultsmentioning
confidence: 99%